Antiphospholipid syndrome - Vicente, Inês (1999)
The authors present the case of a 25 year-old patient, admitted to the Internai Medicine ward of the Centro Hospitalar de Coimbra,for fever syndrome. The clinicai picture and complementary investigations (echocardiography) allowed the diagnosis of Bacterial endocarditis to be made. The persistence of fever, after the disappearance of the endocardial vegetations, in association with a history of deep venous thrombosis and high titres for anti-cardiolipin antibodies (IgG> JOOU GPL); lead to the institution of corticosteroid therapy, with a successful resolution of the clinical picture, and allowed us to reach the final diagnosis - antiphospholipid syndrome.